2005
DOI: 10.1051/0004-6361:20042477
|View full text |Cite
|
Sign up to set email alerts
|

High resolutionHband imaging polarimetry of IRC +10216

Abstract: Abstract. We have carried out an H band imaging polarimetry of an evolved AGB star IRC +10216 using CIAO and AO on the Subaru telescope. Our polarimetric images show NE-S bipolar lobes, a NW lobe, a discrete NW arc with ∼4. 2 radius and two new features of a fan-like shape at the SE and of an elliptic shape at the NW with small polarizations (P < 4%) near the intensity peak. The polarization vectors in the NE-S lobes and the NW lobe have a centrosymmetric pattern centered at the position of the illumination so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 28 publications
8
43
1
Order By: Relevance
“…Since there is no bright single star near Frosty Leo which would be appropriate for AO wavefront sensing (m R brighter than 16 mag and a separation less than 20 ) and the target is sufficiently bright at λ ∼ 0.8 μm for wavefront sensing (m R = 9.7), on-source AO wavefront sensing was applied. We followed the observation sequence described in a previous paper (Murakawa et al 2005). In order to measure the linear polarization, we obtained four sets of images with half-wave plate (HWP) orientations of 0…”
Section: Hk-band Ao Imaging Polarimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no bright single star near Frosty Leo which would be appropriate for AO wavefront sensing (m R brighter than 16 mag and a separation less than 20 ) and the target is sufficiently bright at λ ∼ 0.8 μm for wavefront sensing (m R = 9.7), on-source AO wavefront sensing was applied. We followed the observation sequence described in a previous paper (Murakawa et al 2005). In order to measure the linear polarization, we obtained four sets of images with half-wave plate (HWP) orientations of 0…”
Section: Hk-band Ao Imaging Polarimetrymentioning
confidence: 99%
“…We reduced the recorded data as described in our previous papers (Murakawa et al 2004(Murakawa et al , 2005. After preprocessing (subtraction of the dark frame and flat fielding), we obtained images of the Stokes IQU parameters, the degree of polarization (P), the polarization position angle (θ), as well as their error images.…”
Section: Hk-band Ao Imaging Polarimetrymentioning
confidence: 99%
“…Although it is inconclusive whether these flows are parts of a general equatorial rotation (e.g., Kastner et al 2001), it is not inconceivable that there are multiple outflows on the equatorial plane. For example, Murakawa et al (2005) have suggested that some of the multiple lobes seen in the shell of an AGB star, IRC +10 216 (considered less evolved than the Egg on a similar evolutionary path), are actually due to scattered starlight that has leaked out of the central dust torus through fissures in the torus.…”
Section: Outflow Structure In the Nebulamentioning
confidence: 99%
“…The availability of polarimeters on the HST telescope and at large aperture ground based telescopes equipped with Adaptive Optics (AO) have recently allowed probing the asymmetry of dusty shells at sub-arcsec angular scale for sources at different evolutionary stage (see e.g. Gledhill & Takami 2001;Gledhill 2005;Ueta, Murakawa & Meixner 2007;Murakawa et al 2005Murakawa et al , 2008.…”
Section: Fossil Dust Shells In Scattered Lightmentioning
confidence: 99%